Workplace Spirituality as a Precursor to Relationship-Oriented Selling Characteristics - Chawla, Vaibhav; Guda, Sridhar (2013)
Very few studies have looked upon the construct of workplace spirituality in sales organization context. This paper integrates workplace spirituality with sales literature. The paper points out that self-interest transcendence is a common aspect in the workplace spirituality concept which emerged a decade ago and in most of the relationship-oriented selling characteristics—customer orientation, adaptability, service orientation, and ethical selling behavior. Based on the common aspect of self-interest transcendence, we propose that workplace spirituality could be a causal precursor to relationship-oriented selling characteristics. We present guidelines for future research, implications for practice and a few potential downsides of workplace spirituality in sales organization.
Keywords: Workplace Spirituality; Service orientation; Self-interest transcendence; Ethical selling behavior; Customer Orientation; Adaptive selling